Building the Metaverse by Digital Twins at All Scales, State, Relation - Zhihan Lv; Shuxuan Xie; Yuxi Li; M. Shamim Hossain; Abdulmotaleb El Saddik (Virtual Reality & Intelligent Hardware, 2022)
The new-generation information technology development enables Digital Twins to reshape the physical world into the virtual digital space and provide technical support for Metaverse construction. The Metaverse objects can be mesoscale or macro-micro-scales. Metaverse is a complex collection of both solid substances and liquid, gaseous, plasma, and other uncertain states. Additionally, Metaverse integrates the tangibles with social relations, such as interpersonal relations (friendship, love, and blood relations) and the overall social relations (ethics, morality, and law). This work also introduces some principles or laws to construct the Digital Twins model for social relations, such as broken windows theory, small-world phenomenon, survivor bias, and herd behavior. Thus, from multiple angles, it reviews mapping the tangible and intangible real-world objects to the Metaverse using the Digital Twins model.